Preparation method of heat conduction enhanced dual functional phase change composite material with photothermal effect
By modifying the carrier surface and controlling the growth morphology of copper nanoparticles, the prepared phase change composite material solves the problems of leakage and low thermal conductivity of traditional phase change materials, and achieves improved high heat storage density, thermal stability and photothermal conversion capacity, making it suitable for the field of solar thermal power generation.
Patent Information
- Application Number
- CN202310726233.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2026-02-03
- Estimated Expiration
- 2043-06-19
AI Technical Summary
Traditional phase change materials are prone to leakage during phase change and have low thermal conductivity and photothermal conversion capacity, which affects their large-scale application.
By modifying the carrier surface and controlling the growth morphology of copper nanoparticles, a coral-like 3D interconnected thermally conductive network is formed, and a thermally enhanced bifunctional phase change composite material with photothermal effect is prepared, which reduces interfacial thermal resistance and improves thermal conductivity.
It achieves high heat storage density, excellent thermal stability and long service life of phase change composite materials, as well as excellent photothermal conversion capability, making it suitable for the field of solar thermal power generation.
Smart Images

Figure CN116925705B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of phase change materials, in particular to a preparation method of a heat-conducting enhanced dual-functional phase change composite material with photothermal effect. BACKGROUND
[0002] Developing and utilizing renewable energy and improving energy utilization efficiency are the main measures to solve energy shortage and environmental problems. Phase change materials can store heat efficiently by using their latent heat of phase change, and are a very important energy storage material to solve energy crisis and environmental pollution. They have wide application prospects in intelligent buildings, waste heat recovery, electronic device thermal management and solar photothermal utilization. However, traditional organic phase change materials are prone to leakage during phase change, and their heat conduction and photothermal conversion capabilities are often very low. These two fatal defects seriously affect the large-scale application of phase change materials.
[0003] In recent years, in view of the problem of easy leakage of phase change materials, porous materials or nanomaterials are often used to solve the problem, such as copper powder, hierarchical porous carbon, expanded vermiculite, expanded graphite, diatomite, Mxene, boron nitride, etc. Among them, diatomite is often used as an encapsulating material (also known as a carrier, the same below) for phase change materials due to its advantages of abundant porous structure, large specific surface area and strong adsorption capacity. In addition, diatomite has large reserves, low price, light weight and good chemical stability, and is a commonly used material in the field of building, etc. Using diatomite as an encapsulating material for phase change materials is conducive to the large-scale application of phase change energy storage technology in the field of building energy saving, etc. Boron nitride is a two-dimensional sheet material with high thermal conductivity, which is conducive to building good thermal conduction paths in phase change materials. At the same time, boron nitride also has a large specific surface area, which can adsorb more phase change molecules. These advantages can greatly improve the heat storage performance of the composite material.
[0004] In view of the low thermal conductivity of phase change materials, thermal conductive particles are often added to the phase change materials to improve the thermal conductivity, such as blending organic phase change materials such as paraffin, polyethylene glycol and fatty acid with high thermal conductive particles such as metals and carbon materials. However, the service life of the composite phase change material prepared by this method will be greatly reduced due to the agglomeration and deposition of nanoparticles, and the interface thermal resistance caused by direct mixing restricts the further improvement of the thermal conductivity. It is very important to reduce the discontinuity between materials as much as possible to further improve the thermal conductivity of the composite material. SUMMARY
[0005] The purpose of the present application is to solve the problem that the interfacial thermal resistance is large when the phase change material is blended with the heat-conducting particles, thereby restricting the further improvement of the heat-conducting performance, and to provide a preparation method of a heat-conducting enhanced dual-functional phase change composite material with photothermal effect. Since the growth and final morphology of metal nanoparticles are greatly affected by temperature, pH, and complex system (determining the release speed of metal ions in the metal particle-complex), reaction time, and metal ion concentration, the present application controls the morphology growth of the heat-conducting particles on the surface of the carrier by adjusting the temperature and pH, so as to realize the higher improvement of the heat-conducting performance of the prepared composite material. In addition, the large number of copper nanoparticles and the coral-like 3D interconnected micro-nano structure on the surface of the carrier endow the carrier with excellent photothermal conversion capacity. The modified carrier is combined with the phase change material to prepare a heat-conducting enhanced dual-functional composite phase change material with excellent photothermal conversion capacity.
[0006] The present application is implemented by the following technical solutions:
[0007] A preparation method of a heat-conducting enhanced dual-functional phase change composite material with photothermal effect, comprising the following steps:
[0008] (1) adding dopamine hydrochloride into the dispersion liquid of the carrier, and adding ammonia water to adjust the pH of the suspension to 6-9, and then stirring at a constant temperature of 40-50 DEG C for 1-48 hours, and then vacuum filtering the obtained suspension, and washing and vacuum drying the solid powder to obtain the carrier powder modified by polydopamine (PDA) on the surface;
[0009] (2) growing copper nanoparticles on the surface of the carrier powder modified by polydopamine by in-situ reduction growth method to obtain the carrier powder with copper nanoparticles (Cu NPs) grown in-situ on the surface;
[0010] (3) adding the carrier powder obtained in step (2) into the liquid after the solid phase change material is heated and melted into a liquid, and then fully stirring and mixing the obtained mixture at 70-90 DEG C, and then cooling the mixture to room temperature to obtain the heat-conducting enhanced dual-functional phase change composite material.
[0011] Preferably, the carrier in step (1) comprises metal, mineral, polymer, carbon material and composite material.
[0012] Preferably, the carrier dispersion in step (1) is prepared by the following steps: adding the carrier to a mixed solution of water and ethanol, and mixing evenly to obtain a carrier dispersion with a mass concentration of 0.0625-0.25 g / mL. More preferably, the mass concentration of the carrier dispersion is 0.125 g / mL.
[0013] Further preferably, the carrier in step (1) is diatomaceous earth (DT) or boron nitride (BN), and the volume ratio of water to ethanol is 3:1. The diameter of the diatomaceous earth or boron nitride is approximately 30 μm.
[0014] Preferably, the mass ratio of dopamine hydrochloride to the carrier in step (1) is 2:90-110. More preferably, the mass ratio of dopamine hydrochloride to the carrier in step (1) is 2:100.
[0015] Preferably, the specific steps of in-situ growth of copper nanoparticles on the surface of a carrier powder modified with polydopamine using the in-situ reduction growth method in step (2) are as follows:
[0016] a. Dissolve EDTA-2Na·2H2O, H3BO3, and CuCl2·2H2O sequentially in water and mix thoroughly. Then adjust the pH of the mixed solution to 6-9 to obtain the plating solution. The Cu in the plating solution... 2+ The molar concentration of EDTA-2Na·2H2O, H3BO3, and CuCl2·2H2O is 0.02-0.25:(0.08-1):(0.02-0.25). Dimethylamine borane (DMAB) is added to water to obtain a reducing solution with a molar concentration of 0.32-4M.
[0017] b. Add the polydopamine-modified carrier obtained in step (1) to the plating solution to obtain a suspension. Stir the suspension at 40℃-50℃ for 0.8-1.2 hours, then add the reducing solution to the suspension. Cu 2+ The molar ratio of copper nanoparticles to dimethylamine borane is 0.45-7.1:1. The resulting system is reacted at 40℃-50℃ for 5-7 hours. After filtration, washing and vacuum drying, the resulting mixture yields a carrier powder for in-situ reduction growth of copper nanoparticles on the surface.
[0018] Preferably, the loading of phase change material in the thermally enhanced bifunctional phase change composite material described in step (3) is 40%-70%.
[0019] Preferably, the phase change material in step (3) includes paraffin wax (PW) and polyethylene glycol (PEG). More preferably, the paraffin wax and polyethylene glycol are paraffin wax and polyethylene glycol 2000 (PEG 2000) with a melting point of about 50°C.
[0020] This invention also protects the thermally enhanced phase change composite material with photothermal effect obtained by the above preparation method. This phase change composite material has high heat storage density, excellent thermal stability and reliability, and a long service life.
[0021] This invention also protects the application of the thermally enhanced phase change composite material with photothermal effect in the field of solar thermal power generation. The phase change composite material prepared by this invention has excellent photothermal conversion capability and shows broad application prospects in the field of solar thermal power generation.
[0022] Compared with the prior art, the beneficial effects of the present invention are:
[0023] (1) The phase change composite material prepared by this invention has a high heat storage density;
[0024] (2) The phase change composite material prepared by the present invention has a better thermal conductivity improvement than that of the traditional thermally conductive particle blending method;
[0025] (3) The phase change composite material prepared by the present invention has excellent thermal stability and thermal reliability, and a long service life;
[0026] (4) The phase change composite material prepared by the present invention has excellent photothermal conversion ability and shows broad application prospects in the field of photothermal power generation. Attached Figure Description
[0027] Figure 1 The images shown are scanning electron microscope (SEM) images and magnified views of the carrier modified with polydopamine and grown in situ by reduction of copper nanoparticles in Example 1.
[0028] Figure 2 The images shown are scanning electron microscope (SEM) images and magnified views of the carrier modified with polydopamine and grown in situ by reduction of copper nanoparticles in Example 2.
[0029] Figure 3 Thermogravimetric analysis curves of the phase change composite material with diatomaceous earth as a carrier in Example 1 are shown.
[0030] Figure 4 Thermogravimetric analysis curves of the phase change composite material with boron nitride as the carrier in Example 2;
[0031] Figure 5 The image shows the DSC curves of the phase change composite material with diatomaceous earth as a carrier before and after 50 freeze-thaw cycles in Example 1.
[0032] Figure 6 The image shows the DSC curves of the phase change composite material with boron nitride as the carrier before and after 50 freeze-thaw cycles in Example 2.
[0033] Figure 7The thermal conductivity of the phase change composite material with diatomaceous earth as a carrier in Example 1;
[0034] Figure 8 The thermal conductivity of the phase change composite material with boron nitride as a carrier in Example 2;
[0035] Figure 9 The time-temperature curve of the phase change composite material with diatomaceous earth as a carrier in Example 1 under simulated sunlight irradiation;
[0036] Figure 10 The time-temperature curve of the phase change composite material with boron nitride as a carrier in Example 2 under simulated sunlight irradiation;
[0037] Figure 11 Example 3 shows the output current curve of the phase change composite material with diatomaceous earth as a carrier under simulated sunlight irradiation;
[0038] Figure 12 The output current curve of the phase change composite material with boron nitride as the carrier in Application Example 4 is shown under simulated sunlight irradiation. Detailed Implementation
[0039] The present invention will be further described in detail below with reference to the embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions in the art or as recommended by the manufacturer; the raw materials and reagents used, unless otherwise specified, are considered to be commercially available materials and reagents that can be obtained through conventional markets and other commercial channels.
[0040] A method for preparing a thermally enhanced bifunctional phase change composite material with photothermal effect includes the following steps:
[0041] (1) The carrier was added to a mixed solution of distilled water and ethanol and dispersed using ultrasound at room temperature for 1 hour to obtain a dispersion containing the carrier. Then, 0.5-2 g of dopamine hydrochloride was added to the above dispersion. After it was completely dissolved, the mixture was stirred vigorously for 10 minutes. Then, ammonia water was added dropwise while stirring. When the pH of the solution was 6-9, the solution color was observed to gradually turn reddish-brown. The addition of ammonia water was stopped, and dopamine began to be initiated to self-polymerize. The above mixed suspension was transferred to an open container and stirred at 45°C in an air atmosphere for 1-48 hours. To make the dopamine self-polymerization reaction more complete, the stirring speed was adjusted to 1600 r / min. After the dopamine was fully self-polymerized on the surface of the carrier, the suspension was vacuum filtered. The resulting powder was washed several times with deionized water and anhydrous ethanol, and finally dried in a vacuum drying oven at 50°C for 24 hours to obtain a carrier powder modified with polydopamine (PDA).
[0042] (2) Copper nanoparticles (Cu NPs) were grown in situ on the surface of a polydopamine-modified support using an in-situ reduction growth method. First, disodium ethylenediaminetetraacetate dihydrate (EDTA-2Na·2H2O, 1.49-18.62 g, 0.02-0.25 M) and H3BO3 (0.99-12.36 g, 0.08-1 M) were added to 180 mL of deionized water, stirred, and completely dissolved. Then, CuCl2·2H2O (0.66-8.25 g, 0.02-0.25 M) was added to the above solution and dissolved thoroughly. The mixture was then adjusted to pH 6-9 using NaOH. The prepared plating solution was transferred to a 500 mL single-necked flask, and the polydopamine-modified support was added to the flask and uniformly dispersed in the plating solution using ultrasound. Subsequently, the obtained suspension was transferred to a water bath and stirred for 1 hour at 45°C and 800 rpm to promote the full capture of copper ions in the solution by the polydopamine on the carrier surface. Then, 0.3772–4.715 g of DMAB was added to 20 mL of deionized water to prepare a reduction solution. When the DMAB was completely dissolved, the reduction solution was added dropwise to the final plating solution at a rate of 1 drop per second, and the resulting system was reacted at 45°C with stirring at 800 rpm. Finally, the reaction product was filtered, and the resulting solid composite was washed several times with deionized water and anhydrous ethanol. The resulting composite was then placed in a vacuum drying oven and dried at 50°C for 24 hours to obtain a carrier powder from which copper nanoparticles were grown in situ on the surface.
[0043] (3) Place 4g of phase change material into crucibles, and heat the crucibles in an oven at 80°C for 1 hour. After the solid phase change material has completely melted into a liquid, add the carrier from step (2) into the liquid. Stir the resulting mixture thoroughly at 80°C for 2 hours, and then place it in a vacuum environment for bubbling. During this period, stir the mixture every 0.5 hours to prevent solid sedimentation and uneven mixing. Then cool the mixture to room temperature to obtain phase change composite materials with different loading amounts. Take an appropriate amount of the obtained composite phase change material and press it into a disc with a diameter of about 3cm.
[0044] (4) The morphological changes of the carrier before and after modification were observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The thermal storage performance and thermal reliability of the phase change composite material were measured by differential scanning calorimetry (DSC). The thermal reliability of the phase change composite material was verified by thermogravimetric analysis. The leakage prevention performance of the phase change composite material was verified by leakage test. The thermal conductivity of the composite material was measured by thermal conductivity meter. The photothermal conversion efficiency of the phase change composite material was measured and calculated by solar simulator, thermocouple and data logger.
[0045] Step (4) The test temperature ranges for the thermal storage performance and thermal reliability of the phase change composite material are 15℃-75℃ and 10℃-80℃, respectively, with a heating rate of 3℃ / min. The test temperature range for thermal stability is 30℃-700℃, with a heating rate of 10℃ / min.
[0046] The specific method for the leakage prevention test of phase change composite materials is as follows: place the pressed disc on clean filter paper, and then place the sample together with the filter paper on a constant temperature heating platform at 70°C, and record the leakage situation of the sample after different times.
[0047] The intensity of simulated sunlight in the photothermal conversion efficiency measurement of phase change composite materials was 100 mW / cm². -2 .
[0048] Example 1
[0049] A method for preparing a thermally enhanced bifunctional phase change composite material with photothermal effect includes the following steps:
[0050] (1) First, 100g of diatomaceous earth was added to a mixed solution of 600mL distilled water and 200mL ethanol and dispersed using ultrasound at room temperature for 1 hour. Then, 2g of dopamine hydrochloride was added to the above dispersion and stirred vigorously for 10 minutes after it was completely dissolved. Then, ammonia water was added dropwise while stirring until the solution pH = 8.5. The solution color was observed to gradually turn reddish-brown. The addition of ammonia water was stopped, and dopamine began to be initiated to polymerize. The above mixed suspension was transferred to an open container and stirred at a constant temperature of 45°C in air atmosphere for 48 hours. In order to make the dopamine self-polymerization reaction more complete, the stirring speed was adjusted to 1600r / min. After dopamine fully self-polymerizes on the carrier surface, the suspension is vacuum filtered, and the resulting powder is washed several times with deionized water and anhydrous ethanol. Finally, it is dried in a vacuum drying oven at 50°C for 24 hours. The carrier powder modified with polydopamine is obtained after drying and named DT / PDA. Similarly, the control group is prepared in deionized water using the same procedure, and the resulting unmodified diatomaceous earth powder is named DT.
[0051] (2) Copper nanoparticles were grown in situ on a polydopamine-modified diatomaceous earth surface using an in-situ reduction growth method. First, disodium ethylenediaminetetraacetate dihydrate (EDTA-2Na·2H2O, 18.62 g, 0.25 M) and H3BO3 (12.36 g, 1 M) were added to 180 mL of deionized water, stirred, and completely dissolved. Then, CuCl2·2H2O (8.25 g, 0.25 M) was added to the above solution and dissolved thoroughly. The mixture was then adjusted to pH 8.0 using NaOH. The prepared plating solution was transferred to a 500 mL single-necked flask. The polydopamine-modified support was then added to the flask and uniformly dispersed in the plating solution using ultrasound. Subsequently, the resulting suspension was transferred to a water bath and stirred for 1 hour at 45 °C and 800 r / min to allow the polydopamine on the support surface to fully capture copper ions in the solution. Next, 4.715 g of DMAB was added to 20 mL of deionized water to prepare a reducing solution. When the DMAB was completely dissolved, the reducing solution was added dropwise to the final plating solution at a rate of 1 drop per second. The resulting system was then reacted at 45 °C with a stirring speed of 800 r / min. Finally, the reaction product was filtered, and the resulting solid composite was washed several times with deionized water and anhydrous ethanol. The resulting composite was then placed in a vacuum drying oven and dried at 50 °C for 24 hours to obtain diatomaceous earth powder DT / PDA / Cu, formed by in-situ reduction growth of copper nanoparticles on the surface. Using the original support without polydopamine modification, copper was in-situ reduced on the surface of the original support using the same method to obtain DT / Cu powder.
[0052] (3) Divide 16g of paraffin wax (melting point around 50℃) into four equal portions and place them in crucibles. Then heat the crucibles in an oven at 80℃ for 1 hour. After the solid phase change material has completely melted into a liquid, add 4g of DT, DT / Cu, DT / PDA, and DT / PDA / Cu to the liquid respectively. Stir the resulting mixture thoroughly at 80℃ for 2 hours, and then place it in a vacuum environment for bubbling. During this period, stir the mixture every 0.5 hours to prevent solid sedimentation and uneven mixing. Then cool the mixture to room temperature to obtain a phase change composite material with a theoretical paraffin wax loading of 50%, named PW / DT / PDA / Cu, PW / DT / Cu, PW / DT / PDA, and PW / DT respectively. Take an appropriate amount of the obtained composite phase change material and press it into a disc with a diameter of about 3cm.
[0053] (4) The morphological changes of the carrier before and after modification were observed using scanning electron microscopy and transmission electron microscopy. The thermal storage performance and thermal reliability of the phase change composite material were measured using differential scanning calorimetry (DSC). The thermal reliability of the phase change composite material was verified using thermogravimetric analyzer. The leakage prevention performance of the phase change composite material was verified using leakage test. The thermal conductivity of the composite material was measured using thermal conductivity meter. The photothermal conversion efficiency of the phase change composite material was measured and calculated using solar simulator, thermocouple, and data logger.
[0054] As shown in Table 1, under the same loading rate, due to the modification of PDA and the in-situ reduction growth of Cu NPs, the modified diatomaceous earth has the effect of improving the heat storage density of the phase change material. PW / DT / PDA / Cu has a phase change enthalpy of 80.5 J / g, which is higher than that of other control groups.
[0055] like Figure 1 As shown, copper nanoparticles are distributed in large quantities, uniformly, densely, and continuously on the surface of diatomaceous earth, forming a coral-like 3D interconnected thermally conductive network. This structure helps to significantly reduce interfacial thermal resistance, further improve the thermal conductivity of the composite material, and prevent phase separation caused by the aggregation and sedimentation of thermally conductive particles during long-term use.
[0056] like Figure 3 As shown, PW / DT / PDA / Cu only begins to decompose at 170℃, which is much higher than its operating temperature (around 50℃). Furthermore, the dense Cu NPs on the surface of DT / PDA / Cu form many micropores, in which phase change molecules reside, thus slowing down the decomposition rate. Its decomposition rate is lower than that of other control groups, indicating excellent thermal stability.
[0057] like Figure 5 As shown, the DSC curves of PW / DT / PDA / Cu basically overlapped before and after 50 freeze-thaw cycles, and the phase transformation characteristics did not change significantly, indicating good thermal reliability.
[0058] Figure 7 The results show that the thermal conductivity of PW / DT / PDA / Cu reaches 1.115 W / m K, which is 3.93 times that of pure paraffin and 2.00 times that of PW / DT / Cu. This is due to the dense, continuous, and uniform coral-like interconnection network of Cu NPs on the surface of DT / PDA / Cu, which significantly reduces the interfacial thermal resistance of PW / DT / PDA / Cu and forms a good thermal conduction path, further improving the thermal conductivity compared to PW / DT / Cu.
[0059] like Figure 9As shown, the photothermal conversion efficiency of PW / DT / PDA / Cu reaches 88.27%, which is higher than that of PW / DT / Cu (63.94%). This is due to the large number of photothermal conversion units Cu NPs on the surface of DT / PDA / Cu, the rich multi-level reflection structure (micropores formed by dense and continuous Cu NPs), the enhanced thermal conductivity, and the heat storage density.
[0060] Table 1. Specific phase change parameters of pure paraffin and phase change composite materials.
[0061]
[0062] Example 2
[0063] A method for preparing a thermally enhanced bifunctional phase change composite material with photothermal effect includes the following steps:
[0064] (1) First, add 100g of boron nitride to a mixed solution of 600mL of distilled water and 200mL of ethanol, and disperse it using ultrasound at room temperature for 1 hour. Then add 2g of dopamine hydrochloride to the above dispersion, and stir vigorously for 10 minutes after it is completely dissolved. Then add ammonia dropwise while stirring until the solution pH = 8.5. When the solution color gradually turns reddish-brown, stop adding ammonia. Dopamine begins to be initiated to polymerize. Transfer the above mixed suspension to an open container and stir at a constant temperature of 45°C in air atmosphere for 48 hours. To make the dopamine self-polymerization reaction more complete, adjust the stirring speed to 1600r / min. After dopamine fully self-polymerizes on the surface of boron nitride, the suspension is vacuum filtered, and the resulting powder is washed several times with deionized water and anhydrous ethanol. Finally, it is dried in a vacuum drying oven at 50°C for 24 hours. The resulting carrier powder modified with polydopamine is named BN / PDA. Similarly, the control group is prepared in deionized water using the same procedure, and the resulting unmodified boron nitride powder is named BN.
[0065] (2) Copper nanoparticles were grown in situ on a boron nitride surface modified with polydopamine using an in-situ reduction growth method. First, disodium ethylenediaminetetraacetate dihydrate (EDTA-2Na·2H2O, 18.62 g, 0.25 M) and H3BO3 (12.36 g, 1 M) were added to 180 mL of deionized water, stirred, and completely dissolved. Then, CuCl2·2H2O (8.25 g, 0.25 M) was added to the above solution and dissolved thoroughly. The mixture was then adjusted to pH 8.0 using NaOH. The prepared plating solution was transferred to a 500 mL single-necked flask. The polydopamine-modified support was then added to the flask and uniformly dispersed in the plating solution using ultrasound. Subsequently, the resulting suspension was transferred to a water bath and stirred for 1 hour at 45 °C and 800 r / min to allow the polydopamine on the support surface to fully capture copper ions in the solution. Next, 4.715 g of DMAB was added to 20 mL of deionized water to prepare a reducing solution. When the DMAB was completely dissolved, the reducing solution was added dropwise to the final plating solution at a rate of 1 drop per second. The resulting system was then reacted at 45 °C with a stirring speed of 800 r / min. Finally, the reaction product was filtered, and the resulting solid composite was washed several times with deionized water and anhydrous ethanol. The composite was then placed in a vacuum drying oven and dried at 50 °C for 24 hours to obtain boron nitride powder (BN / PDA / Cu) grown in situ on the surface of copper nanoparticles. Using the original support without polydopamine modification, copper was reduced in situ on the surface of the original support using the same method, resulting in powder BN / Cu.
[0066] (3) Divide 28g of polyethylene glycol 2000 (melting point around 50℃) into four equal portions and place them in crucibles. Then heat the crucibles in an oven at 80℃ for 1 hour. After the solid phase change material has completely melted into a liquid, add 3g each of BN, BN / Cu, BN / PDA, and BN / PDA / Cu to the liquid. Stir the resulting mixture thoroughly at 80℃ for 2 hours, and then place it in a vacuum environment for bubbling. During this period, stir the mixture every 0.5 hours to prevent solid sedimentation and uneven mixing. Then cool the mixture to room temperature to obtain phase change composite materials PEG / BN / PDA / Cu, PEG / BN / Cu, PEG / BN / PDA, and PEG / BN with a theoretical loading of 70%. Take an appropriate amount of the obtained composite phase change material and press it into a disc with a diameter of about 3cm.
[0067] (4) The morphological changes of the carrier before and after modification were observed using scanning electron microscopy and transmission electron microscopy. The thermal storage performance and thermal reliability of the phase change composite material were measured using differential scanning calorimetry (DSC). The thermal reliability of the phase change composite material was verified using thermogravimetric analyzer. The leakage prevention performance of the phase change composite material was verified using leakage test. The thermal conductivity of the composite material was measured using thermal conductivity meter. The photothermal conversion efficiency of the phase change composite material was measured and calculated using solar simulator, thermocouple, and data logger.
[0068] As shown in Table 2, under the same loading rate, due to the modification of PDA and the in-situ reduction growth of Cu NPs, the modified boron nitride has the effect of improving the heat storage density of the phase change material. PEG / BN / PDA / Cu has a phase change enthalpy of 160.7 J / g, which is higher than that of other control groups.
[0069] like Figure 2 As shown, copper nanoparticles on the boron nitride surface are abundant, uniform, dense, and continuously distributed, forming a coral-like 3D interconnected micro-nano thermally conductive network. This structure helps to significantly reduce interfacial thermal resistance and further improve the thermal conductivity of the composite material. At the same time, it prevents phase separation caused by the aggregation and sedimentation of thermally conductive particles during long-term use. In addition, the porous micro-nano structure constructed on the carrier surface is conducive to the adhesion of phase change molecules, increasing the loading rate of phase change material in the modified carrier, thereby improving the heat storage density. This view is confirmed in Table 2.
[0070] like Figure 4 As shown, PEG / BN / PDA / Cu only begins to decompose at 350℃, which is much higher than its operating temperature (around 50℃). Furthermore, the dense Cu NPs on the surface of BN / PDA / Cu form many micropores, in which phase change molecules reside, thus slowing down the decomposition rate. Its decomposition rate is lower than that of other control groups, indicating excellent thermal stability.
[0071] like Figure 6 As shown, the DSC curves of PEG / BN / PDA / Cu before and after 50 freeze-thaw cycles basically overlapped, and the phase transformation characteristics did not change significantly, indicating good thermal reliability.
[0072] Figure 8 The results show that the thermal conductivity of PEG / BN / PDA / Cu reaches 5.741 W / m K, which is 18.88 times that of pure polyethylene glycol and 1.16 times that of PEG / BN / Cu. This is due to the dense, continuous, and uniform coral-like interconnection network of Cu NPs on the surface of BN / PDA / Cu, which significantly reduces the interfacial thermal resistance of PEG / BN / PDA / Cu and forms a good thermal conduction path, further improving the thermal conductivity compared to PEG / BN / Cu.
[0073] like Figure 10As shown, the photothermal conversion efficiency of PEG / BN / PDA / Cu reaches 93.29%, which is higher than that of PEG / BN / Cu (71.50%). This is due to the large number of photothermal conversion units Cu NPs on the surface of BN / PDA / Cu, the rich multi-level reflection structure (micropores formed by dense and continuous Cu NPs), and the enhanced thermal conductivity and heat storage density.
[0074] Table 2 Phase transformation parameters of phase change composite materials
[0075]
[0076] Application Example 1
[0077] The phase change composite material disc prepared in Example 1 was placed in the center of a self-made insulated box. A hole was made in the top of the insulated box, and a T-type thermocouple was inserted into the center of the disc and connected to a data acquisition instrument (100 mW / cm²). -2 Simulated sunlight was projected onto the upper surface of the sample through holes in an insulated chamber, and the time-temperature curve of the sample under simulated sunlight was recorded. Figure 9 The photothermal conversion efficiency of phase change composite materials is given by the formula. The calculations show that, where m and ΔH are the sample mass and enthalpy of fusion, respectively; P and S are the optical power density and radiant area, respectively; and t is the sample enthalpy of fusion. e and t b The end and start times of the phase transition are shown in Table 3. Due to polydopamine modification, Cu Nps grow continuously, uniformly, and densely on the diatomaceous earth surface, improving the heat storage and thermal conductivity of the phase transition composite material. The photothermal conversion efficiency of PW / DT / PDA / Cu reaches 88.27%, which is better than the photothermal conversion efficiency of PW / DT / Cu without polydopamine modification (63.94%), and even better than most similar materials.
[0078] Table 3 Photothermal conversion parameters of phase change composite materials
[0079]
[0080] Application Example 2
[0081] The phase change composite material disc prepared in Example 2 was placed in the center of a self-made insulated box. A hole was made in the top of the insulated box, and a T-type thermocouple was inserted into the center of the disc and connected to a data acquisition instrument (100 mW / cm²). -2 Simulated sunlight was projected onto the upper surface of the sample through holes in an insulated chamber, and the time-temperature curve of the sample under simulated sunlight was recorded. Figure 10 The photothermal conversion efficiency of phase change composite materials is given by the formula. The calculations show that, where m and ΔH are the sample mass and enthalpy of fusion, respectively; P and S are the optical power density and irradiated area, respectively; and t is the sample irradiance. e and t b The end and start times of the phase transition are shown in Table 4. Due to the continuous, uniform, and dense growth of Cu Nps on the boron nitride surface caused by polydopamine modification, the heat storage and thermal conductivity of the phase transition composite material are improved. The photothermal conversion efficiency of PEG / BN / PDA / Cu reaches 93.29%, which is better than that of PEG / BN / Cu without polydopamine modification (71.50%), and even better than most similar materials.
[0082] Table 4 Photothermal conversion parameters of phase change composite materials
[0083]
[0084] Application Example 3
[0085] A thermoelectric generator (also called a thermoelectric generator) is a device that generates voltage through the temperature difference between its two ends, utilizing the Seebeck effect. This invention uses this device to design a continuous light-thermal-electric power generation experiment. Specifically, a phase change composite material, under sunlight, converts and stores light and heat energy (a convex lens is placed between the simulated sunlight and the phase change composite material to concentrate the light beam and increase the irradiation intensity). A thermoelectric generator is placed at the lower end of the phase change composite material prepared in Example 1, and a constant-temperature liquid cooling device (20°C, achieved by circulating constant-temperature water) is connected to its lower surface. The heat stored in the phase change material is continuously released as the material dissipates heat, creating a temperature difference between the upper and lower surfaces of the radiator. The generator outputs voltage. Simultaneously, due to continuous sunlight, the heat released by the phase change material is continuously replenished through the light-thermal effect, enabling the thermoelectric generator to continuously output a stable voltage. Figure 11 As shown, after two hours of continuous sunlight irradiation, the highest output voltages of the thermoelectric generators PW / DT / Cu, PW / DT / PDA, and PW / DT / PDA / Cu are 22mA, 30mA, and 39mA, respectively. This difference is mainly due to the difference in photothermal conversion capability and thermal conductivity. In practical applications, a large current output can be achieved by increasing the irradiation area, the amount of phase change composite material used, and connecting multiple power generation devices in series and parallel.
[0086] Application Example 4
[0087] In Example 2, a thermoelectric generator was placed at the lower end of the phase change composite material. A constant-temperature liquid cooling device (20°C, achieved by circulating constant-temperature water) was connected to its lower surface. The heat stored in the phase change material was continuously released as the material dissipated heat, creating a temperature difference between the upper and lower surfaces of the radiator. The generator output voltage. Simultaneously, due to continuous sunlight, the heat released by the phase change material was continuously replenished through the photothermal effect, enabling the thermoelectric generator to continuously output a stable voltage. Figure 12 As shown, after two hours of continuous sunlight exposure, the highest output voltages of the thermoelectric generators for PEG / PDA, PEG / BN / Cu, and PEG / BN / PDA / Cu are 39mA, 51mA, and 62mA, respectively. This difference is mainly due to the difference in photothermal conversion capability and thermal conductivity. In practical applications, a large current output can be achieved by increasing the irradiation area, the amount of phase change composite material used, and connecting multiple power generation devices in series and parallel.
[0088] Example 3
[0089] Same as Example 1, except that:
[0090] In step (1), the mass concentration of the carrier dispersion is 0.0625 g / mL, and the mass ratio of dopamine hydrochloride to the carrier is 2:90.
[0091] Step (2) Cu in the plating solution 2+ The molar concentration of EDTA-2Na·2H2O, H3BO3, and CuCl2·2H2O was 0.02 M. The molar ratio of EDTA-2Na·2H2O, H3BO3, and CuCl2·2H2O was 1:4:1. Dimethylamine borane was added to water to obtain a reducing solution with a molar concentration of 0.32 M. The suspension was stirred at 40 °C for 1.2 hours, and then the reducing solution was added to the suspension. 2+ The molar ratio of dimethylamineborane to 0.45:1 was used to react the resulting system at 40°C for 7 hours.
[0092] In step (3), the loading of phase change material in the thermally conductive reinforced phase change composite material is 40%.
[0093] Example 4
[0094] Same as Example 1, except that:
[0095] In step (1), the mass concentration of the carrier dispersion is 0.25 g / mL, and the mass ratio of dopamine hydrochloride to the carrier is 2:110.
[0096] Step (2) Cu in the plating solution 2+The molar concentration of EDTA-2Na·2H2O, H3BO3, and CuCl2·2H2O was 0.25 M. The molar ratio of EDTA-2Na·2H2O, H3BO3, and CuCl2·2H2O was 3.125:1:3.125. Dimethylamine borane was added to water to obtain a reducing solution with a molar concentration of 4 M. The suspension was stirred at 50 °C for 0.8 hours, and then the reducing solution was added to the suspension. 2+ The molar ratio of dimethylamineborane to 7.1:1 was used to react the resulting system at 50°C for 5 hours.
[0097] In step (3), the loading of phase change material in the thermally conductive reinforced phase change composite material is 70%.
[0098] The above description of the embodiments is only for the purpose of helping to understand the technical solution and core idea of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principle of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a thermally enhanced bifunctional phase change composite material with photothermal effect, characterized in that, Includes the following steps: (1) Add dopamine hydrochloride to the dispersion of the carrier, and add ammonia water to adjust the pH of the suspension to 6-9. Stir at 40℃-50℃ for 1-48 hours. After vacuum filtering, the solid powder is washed and vacuum dried to obtain the carrier powder modified with polydopamine. The dispersion of the carrier is prepared by the following steps: add the carrier to a mixed solution of water and ethanol, mix evenly to obtain a carrier dispersion with a mass concentration of 0.0625-0.25 g / mL. The carrier is diatomaceous earth or boron nitride. (2) Copper nanoparticles were grown in situ on the surface of a carrier powder modified with polydopamine using an in-situ reduction growth method to obtain a carrier powder in which copper nanoparticles were grown in situ. The specific steps are as follows: a. Dissolve EDTA-2Na·2H2O, H3BO3, and CuCl2·2H2O sequentially in water and mix thoroughly. Then adjust the pH of the mixed solution to 6-9 to obtain the plating solution. The Cu in the plating solution... 2+ The molar concentration of EDTA-2Na·2H2O, H3BO3, and CuCl2·2H2O is 0.02-0.25 M; the molar ratio of EDTA-2Na·2H2O, H3BO3, and CuCl2·2H2O is (0.02-0.25):(0.08-1):(0.02-0.25). Dimethylamine borane is added to water to obtain a reducing solution with a molar concentration of 0.32-4 M. b. Add the polydopamine-modified carrier obtained in step (1) to the plating solution to obtain a suspension. Stir the suspension at 40℃-50℃ for 0.8-1.2 hours, and then slowly add the reducing solution dropwise to the suspension. Cu 2+ The molar ratio of copper nanoparticles to dimethylamine borane is 0.45-7.1:
1. The resulting system is reacted at 40℃-50℃ for 5-7 hours. After filtration, washing and vacuum drying, the resulting mixture yields a carrier powder for in-situ reduction growth of copper nanoparticles on the surface. (3) After heating and melting the solid phase change material into a liquid, the carrier powder obtained in step (2) is added to the liquid. The resulting mixture is stirred and mixed thoroughly at 70℃-90℃ and cooled to room temperature to obtain the thermally enhanced bifunctional phase change composite material.
2. The preparation method according to claim 1, characterized in that, The volume ratio of water to ethanol in step (1) is 3:
1.
3. The preparation method according to claim 1 or 2, characterized in that, The mass ratio of dopamine hydrochloride to carrier in step (1) is 2:90-110.
4. The preparation method according to claim 1, characterized in that, The loading of phase change material in the thermally enhanced bifunctional phase change composite material described in step (3) is 40%-70%.
5. The preparation method according to claim 1 or 4, characterized in that, The phase change material mentioned in step (3) includes paraffin and polyethylene glycol.
6. The thermally conductive enhanced bifunctional phase change composite material with photothermal effect obtained by the preparation method of the photothermal effect-enhanced bifunctional phase change composite material according to claim 1.
7. The application of the thermally enhanced bifunctional phase change composite material with photothermal effect as described in claim 6 in the field of solar thermal power generation.